Protocol for the scoping and case study of nutrition-sensitive agri-food systems interventions in the Mekong Delta, Cambodia - Nabuuma, Deborah; Huynh, Tuyen; Pham, Huong; Duong, Thanh; Thy, Or; Chuon, Sophea; Monville-Oro, Emilita (2023)
This document lays out the protocol for the scoping and case studies of nutrition- and gender-sensitive agri-food system interventions in the Mekong Delta in Cambodia. The studies will generate evidence and information contributing to the co-design of the menu of appropriate nutrition-sensitive agri-food systems interventions and policies and guidelines for implementing nutrient-sensitive actions in deltaic food systems.